2020
DOI: 10.1021/acssuschemeng.0c04980
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymers from Urban Organic Waste: Influence of the Solid Retention Time to Cycle Length Ratio in the Enrichment of a Mixed Microbial Culture (MMC)

Abstract: In this study, the performance of the selection process for polyhydroxyalkanoate (PHA) production from mixed microbial cultures (MMCs) at pilot scale was deeply investigated with the solid retention time (SRT) to cycle length (CL) ratio as main affecting parameter. Four different runs were tested by varying the SRT/CL ratio maintaining the same organic loading rate (OLR). The pilot-scale selection and accumulation reactors were fed with a fermented mixture of source-selected organic fraction of municipal solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 45 publications
(78 reference statements)
2
16
0
Order By: Relevance
“…The PHA-producing process using MMC was recently implemented at a pilot scale. However, the low global volumetric productivity obtained is considered as one of the major constraints for full-scale application, given the great impact of the capital costs on the polymer end-price . Techno-economic analyses have indicated that other critical parameters to be maximized to increase the viability of the process are the overall PHA yield, to minimize the waste of resources, and the PHA content on biomass at the end of production, to reduce extraction costs. , Lastly, the recovery and purification of the polymer is a time-consuming process known to require large amounts of chemicals that also contribute significantly to increase the overall manufacturing costs of the product …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PHA-producing process using MMC was recently implemented at a pilot scale. However, the low global volumetric productivity obtained is considered as one of the major constraints for full-scale application, given the great impact of the capital costs on the polymer end-price . Techno-economic analyses have indicated that other critical parameters to be maximized to increase the viability of the process are the overall PHA yield, to minimize the waste of resources, and the PHA content on biomass at the end of production, to reduce extraction costs. , Lastly, the recovery and purification of the polymer is a time-consuming process known to require large amounts of chemicals that also contribute significantly to increase the overall manufacturing costs of the product …”
Section: Introductionmentioning
confidence: 99%
“…3 Technoeconomic analyses have indicated that other critical parameters to be maximized to increase the viability of the process are the overall PHA yield, to minimize the waste of resources, and the PHA content on biomass at the end of production, to reduce extraction costs. 3,9 Lastly, the recovery and purification of the polymer is a time-consuming process known to require large amounts of chemicals that also contribute significantly to increase the overall manufacturing costs of the product. 10 Several individual factors have been found to contribute to improving the global process performance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the context of waste utilization, MMC-PHA production can be easily integrated into existing infrastructures for the biological treatment of organic waste residues and wastewaters [45]. In the last decade, many research groups have contributed to the scalingup of the process from laboratory-scale experiments to new and integrated pilot-scale facilities [46][47][48][49][50][51][52][53][54]. Regardless of the operating conditions and the adopted scale of the application, the inoculum typically used for MMC systems is the activated sludge from municipal wastewater treatment plants [25].…”
Section: Bioprocess For Pha Production From Terrestrial Bacterial Str...mentioning
confidence: 99%
“…Both of these conditions force a physiological adaptation in those microorganisms that are fast enough and able to thrive under such unbalanced growth conditions-accumulating the external C source as PHA in the feast phase and using it as C-reserve to grow in the famine phase [22]. The optimal operating conditions of each single stage have been largely investigated in the literature (at the laboratory and pilot scale)-the overall process performance is basically calculated as the overall yield of synthetized PHA per kg of VS (volatile solids) in the waste feedstock [49,50,58]. An essential requirement for efficient microbial selection is the application of dynamic feeding conditions, which are generally characterized by transient C source availability, whereby microorganisms are faced with an alteration between high (feast) and low or zero (famine), concentrations of external organic substrate.…”
Section: Role Of the "Feast And Famine Regime" In Mmc-pha Production ...mentioning
confidence: 99%
See 1 more Smart Citation